Emergency Department Observation Unit Utilization Among Older Patients With Chest Pain. Issue 1 (March 2019) - Madsen, Troy; Perkins, Rachelle; Holt, Brennen; Carlson, Margaret; Steenblik, Jacob; Bossart, Philip; Hartsell, Stephen
Abstract : Background: Although some emergency department observation units (EDOUs) may exclude patients over 65 years old, our EDOU accepts patients up to 79 years old. We assessed the utilization of our EDOU by older patients (those 65–79 years old). Methods: We prospectively enrolled emergency department (ED) patients with chest pain. We gathered baseline data at the time of ED presentation and tracked outcomes related to the ED stay, EDOU, and/or inpatient admission. Our primary outcome included EDOU placement among older patients. Our secondary outcome was the rate of major adverse cardiac events [MACE: myocardial infarction, stent, coronary artery bypass graft, and death]. Results: Over the 5-year study period, we evaluated 2242 ED patients with chest pain, of whom 19.4% (95% confidence interval, 17.8%–21.1%) were 65–79 years old. Older patients were more likely to be placed in the EDOU after the ED visit (45.8% vs. 36.6%; P = 0.001) and more likely to be admitted to an inpatient unit from the ED (31.8% vs. 17.9%; P < 0.001) than those under 65 years old. The overall MACE rate was similar between admitted older patients and those in the EDOU: 5.9% versus 4.3% ( P = 0.57). Of the admitted older patients, 30.4% (95% confidence interval, 22.3%–39.9%) were low risk and there were no cases of MACE in this group. Conclusions: In an EDOU that allows older patients, we noted substantial utilization by these patients for the evaluation of chest pain. The characteristics of admitted older patients suggest the potential for even greater EDOU utilization in this group.